Diagnostic Accuracy of Three-Dimensional Endoanal Ultrasound for Anal Fistula: A Systematic Review and Meta-analysis - Li, Jin; Chen, Shao-Na; Lin, Yun-Yong; Zhu, Zhi-Min; Ye, Da-Lin; Chen, Fei; Qiu, Shao-Dong (Turkish Journal of Gastroenterology, 2021)
Background: Anal fistula is a relatively common anorectal disease. An accurate assessment of the main anal fistula type and theanatomy of the internal opening before surgery is necessary to obtain the best surgical results. Whether three-dimensional endoanalultrasound (3D-EAUS) should be used as the first-line diagnostic tool for anal fistula is still controversial. The purpose of this study is toconduct a meta-analysis of the published literature on 3D-EAUS and anal fistula, and compare the results of 3D-EAUS and surgery toevaluate the diagnostic value of 3D-EAUS for anal fistula.Methods: An online search of databases in English included PubMed, Embase, and Cochrane Library. After the diagnostic accuracy of3D-EAUS of all anal fistula types was integrated, a single-group rate meta-analysis was performed; we analyzed 3D-EAUS separatelyfor the diagnosis of different anal fistula types, and conducted a meta-analysis of test accuracy. The analysis combined sensitivity,specificity, and the respective 95% CI, to draw a summary receiver operating characteristic curve (SROC), and estimate the area undercurve (AUC).Results: Based on the inclusion criteria, we selected 8 studies covering 1057 cases of anal fistula and 548 cases of internal opening. Themeta-analysis data show that 3D-EAUS has a total accuracy rate of 91% (95% CI, 88-94%). It has high sensitivity and specificity fordifferent anal fistula classifications. The SROC curves for anal fistula internal openings were plotted, and the AUC was calculated to be0.86 (95% CI, 0.83-0.89).Conclusions: 3D-EAUS can be used as the first-line diagnostic tool for anal fistula, because it has a high diagnostic accuracy for mostanal fistulas. However, due to the insufficient diagnostic accuracy of 3D-EAUS for complex fistulas, 3D-EAUS combined with MRI examination can be used to more accurately detect the secondary extension of complex fistulas, so as to describe the complete anatomy ofthe fistula in more detail.